Size-Based Enrichment Technologies for Non-cancerous Tumor-Derived Cells in Blood. Issue 5 (May 2018) - Mong, Jamie; Tan, Min-Han
Abstract : Enumeration of circulating tumor cells (CTCs) in the bloodstream can predict prognosis and survival in cancer patients. However, CTC rarity and heterogeneity pose challenges in using them as biomarkers. Recent publications have reported new classes of circulating, non-cancerous tumor-derived cells present in cancer patients but not in healthy controls; these include cancer-associated macrophages, tumor-endothelial clusters (TECs), and cancer-associated fibroblasts (CAFs). Well-established marker-dependent CTC enrichment technologies will miss this group of circulating cells. To maximize our chance of finding useful circulating biomarkers in cancer patients, we propose the use of size-based enrichment technologies to isolate both cancerous and non-cancerous cells in circulation. We review their biological properties and discuss device features to consider in their enrichment. Highlights: Captured circulating tumor cells (CTCs) are useful in the diagnosis, prognostication, and treatment of cancer. However, their utility as a biomarker is limited because they are rare and heterogeneous. New classes of tumor-derived yet non-cancerous cells in circulation such as cancer-associated macrophage-like cells (CAMLs) and tumor-endothelial clusters (TECs) may be more prominent than CTCs, especially in the early stages of cancer. To enhance the sensitivity and specificity of circulating cells in cancer diagnostics, we propose the search to be expanded to all tumor-derived cells. In view of recent biological insights, we find size-based, label-free cell-capture approaches more appropriate. Using technologies that have successfully isolated CAMLs and TECs as examples, some important features emerge in device selection. Devices need to be chosen according to the target patient population as well as desired downstream applications.